Public trust in mega event planning institutions: The role of knowledge, transparency and corruption - Nunkoo, R.; Ribeiro, M.; Sunnassee, V.; Gursoy, Dogan (Pergamon, 2018)
The political ramifications of hosting mega-events are huge. In this article, we investigate the relationships among corruption, transparency, knowledge, and public trust using data collected from 3786 Brazilians in the context of the 2014 FIFA World Cup Games. Findings from the structural equation modeling indicate that public trust in government is determined by the respondents’ perceptions of corruption and transparency and their level of knowledge about the roles of government and the local organizing committee in the mega-event. The respondents’ level of trust in the local organizing committee also exerts an influence on their trust in the government. The implications of the findings for governments planning to host mega-events in the future are discussed. This research makes an important contribution to the literature, being the first study to test a theoretical model that analyses the relationships between corruption, transparency, knowledge, and public trust in the context of a mega-sport event.